PERLINDUNGAN TENAGA KERJA INDONESIA MELALUI HUKUM INTERNASIONAL - Dwipayana, Kadek Kresna (Jurnal Pacta Sunt Servanda, 2022)
The purpose of writing this scientific article is to find out what forms of legal protection are given to TKI who work abroad, why TKI should be given legal protection and what factors cause the high number of TKI abroad. The method used in the preparation of this article is the normative method. The results of this study that workers have received legal protection from an organization called the ILO international labor organization, TKI must get this protection so that they have a sense of security and comfort when working abroad, the number of TKI who work abroad is due to the lack of job opportunities. in Indonesia, so they are forced to work as migrant workers abroad.